2019
DOI: 10.1200/jgo.19.00051
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Refractory and Relapsed Hodgkin Lymphoma With Autologous Stem-Cell Transplantation: A Single Institution Experience

Abstract: PURPOSE Hodgkin lymphoma is the most common cancer in children, adolescents, and young adults. Overall survival is approximately 80% to 90%. A subset of these patients has refractory disease or experience disease relapse. Conventional salvage therapies and autologous stem-cell transplantation is usually considered the standard of care for these patients. Our analysis reports outcomes in these patients. PATIENTS AND METHODS After institutional review board approval, a retrospective analysis of patients with Hod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is noteworthy that achieving higher rates of CR, as it was found in private hospitals compared to public institutions, was not translated in an improvement of OS. This may be due to the low percentage of patients who progress, and also probably to the success of the available rescue strategies for patients who are in first relapse or who progress after first-line [20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that achieving higher rates of CR, as it was found in private hospitals compared to public institutions, was not translated in an improvement of OS. This may be due to the low percentage of patients who progress, and also probably to the success of the available rescue strategies for patients who are in first relapse or who progress after first-line [20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…However, an Contrast Media & Molecular Imaging opposite conclusion was drawn among patients who had a PET-CT scan within 3 months after ASCT. is early evaluation could be crucially important because it is performed before the occurrence of relapse in most patients [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…For lymphoma patients receiving ASCT, it has been shown that pretransplant PET-CT status is constantly and strongly associated with outcomes [9][10][11][12][13]. However, the prognostic value of post-ASCT [ 18 F]F-FDG PET-CT still remains controversial.…”
Section: Introductionmentioning
confidence: 99%